Functions of toponyms in novels - Gibka, Martyna Katarzyna (Papers in Linguistics, 2024)
This article is devoted to the functions of toponyms in the novel. The study was undertaken in order to fill a gap in the field of literary onomastics, in which more attention has so far been paid to characters’ names than to place names, and within the research on toponyms no universal method has yet been proposed that could be used to study the functions of these names in any novel. The proposal of such a universal method would enable the further development of research within this topic and the comparison of analyses carried out based on this method. In the long run, it might also have implications for research in the field of translating toponyms in the novel. The starting point for this study is the theory of two acts (which uses the act of naming and the act of using a name). The functions of toponyms in the novel are divided into two groups: permanent and momentary. In the course of the analysis, the anti-didactic function, which has not been identified in any previous studies based on the theory of two acts, was recognised.